2022
DOI: 10.3390/ph15030347
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I Nanoparticles as Curcumin Carriers for Cerebral Endothelial Cells: Improved Cytoprotective Effects against Methylglyoxal

Abstract: Methylglyoxal (MGO) is a highly reactive metabolite of glucose present at elevated levels in diabetic patients. Its cytotoxicity is associated with endothelial dysfunction, which plays a role in cardiovascular and cerebrovascular complications. Although curcumin has many therapeutic benefits, these are limited due to its low bioavailability. We aimed to improve the bioavailability of curcumin and evaluate a potential synergistic effect of curcumin and reconstituted high-density lipoprotein (rHDL) nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Previous studies demonstrated that an imbalance between oxidative stress (ROS and MDA) and antioxidants (SOD and GSH‐Px) is a leading factor of MGO‐induced endothelial cell dysfunction (Narra et al, 2022). To investigate whether umbelliferone has effects in the MGO‐mediated intracellular ROS generation, HUVECs were incubated with umbelliferone (10 and 20 μM) for 2 h and subsequently exposed to MGO (500 mM) for 24 h. It was observed that MGO treatment contributed to significant increase in ROS accumulation and MDA content, which was weakened by umbelliferone (Figure 4A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that an imbalance between oxidative stress (ROS and MDA) and antioxidants (SOD and GSH‐Px) is a leading factor of MGO‐induced endothelial cell dysfunction (Narra et al, 2022). To investigate whether umbelliferone has effects in the MGO‐mediated intracellular ROS generation, HUVECs were incubated with umbelliferone (10 and 20 μM) for 2 h and subsequently exposed to MGO (500 mM) for 24 h. It was observed that MGO treatment contributed to significant increase in ROS accumulation and MDA content, which was weakened by umbelliferone (Figure 4A and B).…”
Section: Resultsmentioning
confidence: 99%
“…They found that Cur-rHDLs(0.2 and 0.4 µM) reduced oxidative stress and endoplasmic reticulum stress(ERS) and played a protective role in the integrity of the endothelial cell barrier. 26 AGEs also have an effect on myocardial inflammation. Sowndhar et al found that dietary curcumin could neutralize AGEs-induced adverse reactions and reduce the expression of pro-inflammatory genes.…”
Section: Inhibits Inflammation Of Vecsmentioning
confidence: 99%